Design and Development Engine Modifications Noken (Camshaf) Stars In SMK Nusantara Thatch - Rais M A (Bandar Lampung University (UBL), 2017)
The purpose of this thesis are: (1) designing a modifiedengine construction design camshaft, (2) to know the ingredients of engine components and to knowcalculation enginemodification, camshaft The (3) determining the transmission range of the engine, (4) with the ability to adjust the electrical power for small to medium workshop which is estimated at between 900 to 1300 watts.This design concept refers to the design concept darmawanie with several stages, among others needs, defining the project and a list of requirements, outlines prancangan product concept, then design products.The results of the design of this machine is made is the result: (1) The design of the engine modifications that are efficient, (2) transmission system engine modification is to change the rotation of the motor power from 1400 rpm to 700 rpm, with a component in the form of 2 puly diameter 3